Análise do efeito da Sequência de Arestas e do Número de Interrupções para medir desgaste na vida da Ferramenta no Torneamento - Pereira, Janaína Aparecida (2009)
Machining experts sometimes come across with a question when using tool tips inserts: The use of one of the edges of an insert affects the performance of the others? Some of them comment that in squares inserts, for instance, the sequence of the tool edges used could affect their lives when machining. The reason for this is that worn edges would adversely affect the wear progress in the next adjacent edges. In order to avoid this, it is recommendable to index only the diagonal sequence of the cutting edges. Based on this hypothesis and because there is no scientific evidence to support it, squared carbide inserts with negative rake angle with eight edges were tested in turning of a microalloyed (HSLA) DIN 38MnSiVS5 steel. Tests were performed using all the possible edges sequences of one tool face in order to verify the possible influences in the tool edge lives. After using the upper face edges, the bottom face edges of the inserts were also tested. Tool flank wear was monitored during machining, criterion chosen as end of life. Replicas were made and the data were analyzed using the software Statistica 7.0 by differences between means with a significance level of 5%. The work also has a second phase of testing where the objective is to verify and compare the influence of the number of stops to measure the wear on tool life. The results showed that, statistically, it cannot be said that the wear of an edge affects the development of the wear, once therefore its life, on the adjacent edge of a square insert, i.e., they showed that the sequence of use of the edges does not influence the tool life of square inserts. However, one should mention that there was a wide dispersion in the results investigated. The results of the second phase of the research showed influential in the tool life. This means that the number of stops conducted to measure the wear influences the development of wear and consequently the tool life of square inserts.